2021
DOI: 10.1080/2162402x.2021.1880046
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of human monocyte-derived suppressor cell-based treatment in graft-versus-host disease prevention while preserving graft-versus-leukemia effect

Abstract: Background Immunosuppressive cell-based therapy is a recent strategy for controlling Graft- versus -Host Disease (GvHD). Such cells ought to maintain their suppressive function in inflammatory conditions and in the presence of immunosuppressive agents currently used in allogeneic hematopoietic cell transplantation (allo-HCT). Moreover, these therapies should not diminish the benefits of allo-HCT, the Graft- versus -Leukemia (GvL) effect. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…We previously showed that CD33+HuMoSC efficiently inhibited T cell proliferation and induced Treg differentiation ( 5 ), independent of cell-to-cell contact. In fact, CD33+HuMoSC culture supernatant induced very strong anti-proliferative effect ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that CD33+HuMoSC efficiently inhibited T cell proliferation and induced Treg differentiation ( 5 ), independent of cell-to-cell contact. In fact, CD33+HuMoSC culture supernatant induced very strong anti-proliferative effect ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mTGF, FasL and PD-L2 expression were very limited in both cells ( Figure 1E ). Considering that CD33+HuMoSC immunosuppressive properties were previously reported ( 4 , 5 ), we were interested in determining whether CD14+HuMoSC supernatant could provide similar effects. In this aim, total PBMC activated by CD3/CD28 beads were cultured in medium supplemented with increasing volumes of CD14+HuMoSC supernatant for five days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations